The mechanisms related to grief and their implications for exposure to HIV - Oliveira, Solange M.S.; Villela, Wilza V. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: the complex relationship between the factors which can be involved in the acquisition of diseases makes it difficult to identify variables andto quantify their influences. This paper aims to discuss ways in which some life moments marked by unconscious psychic mechanisms could be amongthese factors. Objective: describer features of the psychic life of infected individuals in the supposed moment of the HIV exposure. Method: the approachwas qualitative, the interviews were open, non-structured. The interviewees were invited to talk about themselves, their lives and under which circumstan-ces they believed to have become infected. The interviews were analyzed according to psychoanalytic theory, finding in the internal logic of their speechaspects of their emotional lives related to the supposed moment of the infection. Result:all the interviewees, describing aspects of HIV vulnerability intheir lives, related the supposed moment of the infection to situations of loss, which had emotionally disorganized them. Conclusion: an some specificsituations mechanisms related to grief were found, as individual factors of vulnerability to HIV exposure. According to Freudian theory, grief is a reactionto the loss of a loved object, signifying an emptiness of the self, and an over-investment in a sole representation, as an attempt to keep alive the lost object.In these interviewees such reactions are hidden, and a lack of an internal working through of the grief was found. Attempts to reorganize life through thedenial of loss and intensification of the search for new loving relationships were found.